Application of Nanomaterials in the Prevention, Detection, and Treatment of Methicillin-Resistant Staphylococcus aureus (MRSA) - John Hulme (MDPI AG, 2022)
Due to differences in geographic surveillance systems, chemical sanitization practices, and antibiotic stewardship (AS) implementation employed during the COVID-19 pandemic, many experts have expressed concerns regarding a future surge in global antimicrobial resistance (AMR). A potential beneficiary of these differences is the Gram-positive bacteria MRSA. MRSA is a bacterial pathogen with a high potential for mutational resistance, allowing it to engage various AMR mechanisms circumventing conventional antibiotic therapies and the host's immune response. Coupled with a lack of novel FDA-approved antibiotics reaching the clinic, the onus is on researchers to develop alternative treatment tools to mitigate against an increase in pathogenic resistance. Mitigation strategies can take the form of synthetic or biomimetic nanomaterials/vesicles employed in vaccines, rapid diagnostics, antibiotic delivery, and nanotherapeutics. This review seeks to discuss the current potential of the aforementioned nanomaterials in detecting and treating MRSA.